PENGEMBANGAN EKONOMI KREATIF MASYARAKAT BERBASIS MEDIA ONLINE DI DESA SIDOREJO PLAOSAN MAGETAN - Rijal Amirudin; Moh. Irmawan Jauhari (Institut Agama Islam Tribakti Kediri, 2023)
The purpose of this activity is to provide capital-based online marketing training in the community of Sidorejo Village, Plaosan District, Magetan Regency. The result of this community service activity is that an online-based creative economy needs to be developed as a marketing base for UMKM. Where creative economy marketing on social media carried out by the Sidorejo Plaosan Magetan community also collaborates with family members to actively promote. The active role of the Sidorejo community in the creative economy shows that independence is an asset. In addition, the abundance of organic beverage raw materials can cut production costs. The enthusiasm of the Sidorejo people in the online media-based creative economy requires the role of the village government to facilitate a number of things. Such as inviting them to be actively involved in BUMDES, seeking friendly capital, and making it a village brand. So that the village government's response will be able to motivate the community and encourage the development of UMKM.